Fractal dimension and Shannon's entropy analyses of the architectural complexity caused by the inflammatory reactions induced by highly crystalline polyvinyl alcohol) microspheres implanted in subcutaneous tissues of the Wistar rats - Silva, Danilo A. [UNESP]; Basso, Glaucia G. [UNESP]; Semenzim, Vinícius L. [UNESP]; Godoy, Moacir F.; Taboga, Sebastião R. [UNESP]; Andrade, Alexandre L. [UNESP]; Luvizotto, Maria Cecília Rui [UNESP]; Braile, Domingo M.; Nery, Jose G. [UNESP] (Wiley, 2013)
The results of the histopathological analyses after the implantation of highly crystalline PVA microspheres in subcutaneous tissues of Wistar rats are here in reported. Three different groups of PVA microparticles were systematically studied: highly crystalline, amorphous, and commercial ones. In addition to these experiments, complementary analyses of architectural complexity were performed using fractal dimension (FD), and Shannon's entropy (SE) concepts. The highly crystalline microspheres induced inflammatory reactions similar to the ones observed for the commercial ones, while the inflammatory reactions caused by the amorphous ones were less intense. Statistical analyses of the subcutaneous tissues of Wistar rats implanted with the highly crystalline microspheres resulted in FD and SE values significantly higher than the statistical parameters observed for the amorphous ones. The FD and SE parameters obtained for the subcutaneous tissues of Wistar rats implanted with crystalline and commercial microparticles were statistically similar. Briefly, the results indicated that the new highly crystalline microspheres had biocompatible behavior comparable to the commercial ones. In addition, statistical tools such as FD and SE analyses when combined with histopathological analyses can be useful tools to investigate the architectural complexity tissues caused by complex inflammatory reactions. © 2012 WILEY PERIODICALS, INC.
Keywords: Embolization; Fractal dimension; Inflammatory reaction; Poly(vinyl alcohol); Shannon's entropy; Complementary analysis; Histopathological analysis; Micro-particles; Statistical parameters; Statistical tools; Subcutaneous tissues; Wistar rat; Architecture; Finite difference method; Histology; Information theory; Microspheres; Polyvinyl alcohols; Statistical mechanics; Tissue; Crystalline materials; microsphere; polyvinyl alcohol; animal experiment; animal tissue; biocompatibility; chemical structure; controlled study; crystal structure; entropy; fractal analysis; histopathology; inflammation; nonhuman; rat; scanning electron microscopy; subcutaneous tissue; synthesis; X ray diffraction; Animals; Crystallization; Entropy; Fractals; Implants, Experimental; Inflammation; Microscopy, Electron, Scanning; Polyvinyl Alcohol; Rats; Rats, Wistar; Subcutaneous Tissue; X-Ray Diffraction